Modulatory effect of the transmembrane domain of the protein-tyrosine kinase encoded by oncogene ros: biological function and substrate interaction. - Zong, C S (1994)
There is a 3-aa insertion in the transmembrane (TM) domain of the p68gag-ros protein-tyrosine kinase encoded by avian sarcoma virus UR2 v-ros as compared with that of the protooncogene c-ros. The effect of this insertion on biological function and biochemical properties of v-Ros protein was investigated by deleting these 3 aa to generate the mutant TM1. This mutant has greatly reduced transforming, mitogenic, and tumorigenic activities despite the fact that the protein-tyrosine kinase activity and cell-surface localization of TM1 protein are unaffected. However, unlike UR2 protein, mutant TM1 protein becomes glycosylated, is differentially phosphorylated, and fails to induce tyrosine phosphorylation of a 88-kDa protein and a major substrate of insulin receptor, insulin receptor substrate 1. The TM1 protein is unable to associate with phosphatidylinositol 3-kinase and fails to promote association of insulin receptor substrate 1 with phosphatidylinositol 3-kinase. By contrast, tyrosine phosphorylation of Shc protein and phospholipase C gamma as well as interaction of Grb2 protein with Shc and SOS protein signaling components are unaltered in the TM1 infected cells. Our results show that the TM-domain sequence of p68gag-ros profoundly affects its function and substrate interaction. The mutant defines a signaling pathway including phosphatidylinositol 3-kinase, insulin receptor substrate 1, and possibly an 88-kDa protein that does not overlap the Ras pathway and is important for full transforming and mitogenic potency of v-ros protein-tyrosine kinase.